Hart Crane - American Writers 47 : University of Minnesota Pamphlets on American Writers - Spears, Monroe K., 1916-1998 (Book collections on Project MUSE., 1965)
Hart Crane - American Writers 47 was first published in 1965. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.